Tools for assessing quality of life in cardiology and cardiac surgery - Gierlaszyńska, Karolina; Pudlo, Robert; Jaworska, Izabela; Byrczek-Godula, Kamila; Gąsior, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The holistic concept of health, popularization of knowledge, as well as social and economic factors have contributed to the growing interest in research concerning quality of life in cardiovascular diseases. The value of direct measurements of the patient’s well-being and the extent of their functioning in everyday life (i.e., health-related quality of life; HRQoL) has gained appreciation. Questionnaires are the most popular method of measuring quality of life. On the basis of the literature, we can conclude that the Short-Form Health Survey (SF-36) questionnaire is one of the most widely used tools measuring the quality of life of patients undergoing cardiological treatment and cardiac surgery.